2019
DOI: 10.4102/sajip.v45i0.1607
|View full text |Cite
|
Sign up to set email alerts
|

On reproducibility and replicability: Arguing for open science practices and methodological improvements at the South African Journal of Industrial Psychology

Abstract: Problematisation: In recent years, psychology has been going through a crisis of sorts. Research methods and practices have come under increased scrutiny, with many issues identified as negatively contributing to low replicability and reproducibility of psychological research.Implications: As a consequence, researchers are increasingly called upon to overhaul and improve their research process. Various stakeholders within the scientific community are arguing for more openness and rigor within industrial and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(86 citation statements)
references
References 75 publications
(108 reference statements)
1
75
0
Order By: Relevance
“…Psychology is currently facing challenges related to the replicability of the discipline's findings (Efendic & Van Zyl, 2019). Even though this study provides evidence for the existence of personality aspects, albeit not hierarchical aspects, amongst South African employees, the proposed factor structure must be replicated with larger samples than the one used in the current study before definitive statements are made about the manifestation of the 10 personality aspects amongst the facets of the BTI.…”
Section: Discussionmentioning
confidence: 82%
“…Psychology is currently facing challenges related to the replicability of the discipline's findings (Efendic & Van Zyl, 2019). Even though this study provides evidence for the existence of personality aspects, albeit not hierarchical aspects, amongst South African employees, the proposed factor structure must be replicated with larger samples than the one used in the current study before definitive statements are made about the manifestation of the 10 personality aspects amongst the facets of the BTI.…”
Section: Discussionmentioning
confidence: 82%
“…These authors highlighted various systemic causes contributing to the lack of confidence in IOP, ranging from the way in which authors conduct research and process or report results through to how journals, editors and reviewers contribute to such through various editorial processes, policies and practices. Efendic and Van Zyl (2019) briefly demonstrated that these issues are also apparent within SAJIP, highlighting inconsistencies in statistical results reported by authors, that various studies were insufficiently powered, that best-practice guidelines for the reporting of results were mostly only partially followed and that no transparency exists with regard to the research process. In effect, they highlighted that SAJIP's authorship knowingly or unknowingly engages in what Nosek et al (2015Nosek et al ( :1422 call 'questionable research practices', and that the journal is not immune to the issues contributing to the confidence crisis in our discipline.…”
Section: Discussionmentioning
confidence: 99%
“…But how can that be managed? Efendic and Van Zyl (2019) argued that both authors and the journal play an important role in enhancing the credibility of the IOP discipline. They provided detailed descriptions of approaches, research practices and techniques authors could employ to enhance the transparency and quality of their manuscripts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations